From Power to Women’s Empowerment: The Missing Links - Polar, Vivian; Poole, N. (2024)
This chapter explores the instrumentalization of women’s empowerment in agricultural research for development, with particular attention on critically examining how the concept of empowerment has become understood as an externalized process that can be bestowed on women through production-oriented interventions. The chapter explores multiple manifestations of power and depicts their occurrence through experiences of women and men farmers in the Andean region. It analyzes how the use of empowerment has deviated from building agency and disrupting power dynamics, highlighting the need for a feminist and transformative conceptualization and operationalization of empowerment in the agricultural sector.